PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG SISWA SEKOLAH DASAR - Siti Khodijah; Nurhaswinda; Rizki Ananda; Iis Aprinawati; Indriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The background of this research is the low arithmetic ability of first-grade students at UPT SDN 009 Sendayan. This study aims to improve students’ arithmetic skills through the implementation of the Problem Based Learning (PBL) model. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of two meetings. The subjects of this study were 15 first-grade students. Data were collected through observation, tests, and documentation, and analyzed qualitatively and quantitatively.The results show that the implementation of the Problem Based Learning (PBL) model can improve students’ arithmetic ability. The average score increased from 36.18 (very poor category) in the pre-action stage with 13% mastery, to 68.5 (fair category) in cycle I with 60% mastery, and to 86.7 (very good category) in cycle II with 100% mastery. It can be concluded that the Problem Based Learning (PBL) model effectively improves arithmetic skills of first-grade students at UPT SDN 009 Sendayan.